(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2010)
In Brazil, many cases of breast and cervical cancers are only diagnosed in advanced stages. Information on prevention of cancer in women is increasingly available. However, prevention or early treatment alternatives are often not practiced. This study investigated the issues hindering the practice of prevention against cancer in women. A qualitative method was employed in this exploratory and descriptive study. The sample included thirty-three randomly selected women undergoing treatment. The survey data was collected at the South Parana Institute of Oncology, Ponta Grossa - PR in September 2007 using a semi-structured individual interview after approval by the Research Ethics Committee of the Brazilian College of Systemic Studies - CBES, Curitiba - PR, under protocol 0462/07, in compliance with CNS Resolution number 196/96. Absence of symptoms, embarrassment, long waiting list for treatment, and indifference to the campaigns of prevention were some obstacles encountered. A lack of information about cancer and its causes and consequences was the biggest issue found regarding the acceptance of prevention of cancer in women. The pharmacist, in the role of educator in the prevention of cancer in women, can emphasize the importance of regular prevention practices and highlight the implications of late treatment, disseminating information that can have greater impact on society.